RETRACTED ARTICLE: A novel necroptosis signature for predicting survival in lung adenocarcinoma - Kui Zang; Min Wang; Xingxing Zhu; Bin Yao; Ying Huang (BMC, 2023)
Abstract Background To explore the necroptosis-related genes (NRGs) signature and its predictive values in lung adenocarcinoma (LUAD). Methods The training cohort consisted of tumor samples from The Cancer Genome Atlas, and the validation set comprised data from the Gene Expression Omnibus. Univariate and multivariate Cox regression analyses were applied to identify the prognostic NRG signature as an independent molecular indicator. Correlation analysis was used for the association assessment between the NRG signature and immune checkpoint molecules. Results NRGs involved in necroptosis and immune NOD-like receptor signaling. The NRG signature based on eight NRGs can divide tumors into high-risk and low-risk groups, which was significantly associated with worse survival. Multivariate Cox regression analysis showed that this NRG signature remained an independent prognostic indicator. Stratification analyses demonstrated that this NRG signature was still effective for predicting survival in each stratum of age, gender, and tumor stage. The ROC curve showed a good predictive ability using the NRG signature in the validation cohort (AUC = 0.81). The NRG signature was related to immune checkpoint molecules PD − 1, PD-L1, and PD-L2. Conclusions The NRG signature could be a novel predictor of the prognosis and may become a potential therapeutic target in LUAD.